Spermidine enhances heat tolerance of rice seeds during mid-filling stage and promote subsequent seed germination - Huang, Yutao; Mei, Gaofu; Cao, Dongdong; Qin, Yebo; Yang, Liu; Ruan, Xiaoli (Frontiers in Plant Science, 2023)
Heat stress is a vital factor which restricts rice seed quality and yield. However, the response mechanism to heat stress in the mid filling stage of rice seed is unclear. The present study aims to explore technologies for improving rice seeds heat tolerance and subsequent seed germination. We found that spermidine (Spd) application effectively alleviated the damage of heat stress treatment during mid-filling stage (HTM, 12-20 days after pollination) on seed development, promoted subsequent seed germination and seedlings establishment.Spd treatment significantly increased seed dry weight, starch and amylose contents during seed development under heat stress, and improved seed germinate, seedlings establishment and seedling characteristics during germination time. Biochemical analysis indicated that, HTM significantly decreased the activities of several starch-synthase enzymes and led to a decrease in starch content. While Spd treatment significantly enhanced the activities of ADPglucose pyrophosphorylas and granule-bound starch synthase, as well as the correspondinggenes expressions in HTM rice seeds, resulting in the increases of amylose and total starch contents. In addition, Spd significantly increased the catalase and glutathione reductase activities together with corresponding-genes expressions, and lowered the over-accumulation of H2O2 and malondialdehyde in HTM seeds. In the subsequent seed germination process, HTM+Spd seeds exhibited dramatically up-regulated levels of soluble sugars, glucose, ATP and energy charges. Consistently, HTM+Spd seeds showed significantly increased of αamylose and α-glucosidase activities as well as corresponding-genes expressions during early germination. Moreover, HTM evidently increased the abscisic acid (ABA) content, decreased the gibberellin (GA) content, and accordingly significantly declined the GA/ABA ratio during early rice seeds germination. However, Spd treatment did not significantly affect the metabolism of GA and ABA in seed germination stage. The present study suggested that Spd treatment could effectively alleviate the negative impact of HTM on seed development and the subsequent seed germination, which might be closely correlated with starch synthesis and antioxidant defense during seed filling period, starch decomposition and energy supply in seed germination period.